2015
DOI: 10.3390/nu7020905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin Supplementation on Physiological Fatigue and Physical Performance in Mice

Abstract: Curcumin (CCM) is a well-known phytocompound and food component found in the spice turmeric and has multifunctional bioactivities. However, few studies have examined its effects on exercise performance and physical fatigue. We aimed to evaluate the potential beneficial effects of CCM supplementation on fatigue and ergogenic function following physical challenge in mice. Male ICR mice were divided into four groups to receive vehicle or CCM (180 μg/mL) by oral gavage at 0, 12.3, 24.6, or 61.5 mL/kg/day for four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(144 citation statements)
references
References 43 publications
11
131
0
2
Order By: Relevance
“…The results also revealed that the swimming times to exhaustion of the supplemented groups were 36.23 (AVII) and 37.97 (SBWII) per cent longer than that of the control group. Reduction in the physiological fatigue and increase in the physical performance due to supplementation of Curcumin for enhanced muscular glycogen content on Swiss mice was also reported (Huang et al, 2015). In the present study the increase in swimming time with concomitant reduction in fatigue might be due to the presence of health promoting bio constituents present in PHG containing various herbs (Jung et al, 2004).…”
Section: Anti-fatigue Activitysupporting
confidence: 71%
“…The results also revealed that the swimming times to exhaustion of the supplemented groups were 36.23 (AVII) and 37.97 (SBWII) per cent longer than that of the control group. Reduction in the physiological fatigue and increase in the physical performance due to supplementation of Curcumin for enhanced muscular glycogen content on Swiss mice was also reported (Huang et al, 2015). In the present study the increase in swimming time with concomitant reduction in fatigue might be due to the presence of health promoting bio constituents present in PHG containing various herbs (Jung et al, 2004).…”
Section: Anti-fatigue Activitysupporting
confidence: 71%
“…The swimming exercise performance test was performed as previously described [20]. After 4 weeks of CAP supplementation, a lead sheet (5% equivalent to individual body weight) was attached to the tail of mice for exhaustive swimming challenge.…”
Section: Methodsmentioning
confidence: 99%
“…A previous article reviewed the physiological effects on energy metabolism and utilization via TRPV1 activation [15]. Therefore, we conducted this study to evaluate the potential ergogenic and anti-fatigue effects of CAP using our previously established in vivo platform [19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Some investigations have evaluated for the effect of curcumin on DOMS (21)(22)(23)(24). However, to the best of our knowledge, no study to date has tested administration of 150mg curcumin supplement immediately after intensive eccentric exercise.…”
Section: Nakhostinmentioning
confidence: 99%